Role of Flaxseed Meal Feeding for Different Durations in the Lipid Deposition and Meat Quality in Broiler Chickens. (21st January 2019) - Kumar, Faneshwar; Tyagi, Praveen K.; Mir, Nasir Akbar; Tyagi, Pramod K.; Dev, Kapil; Bera, Indrajit; Biswas, Ashim K.; Sharma, Divya; Mandal, Asit Baran; Deo, Chandra
Abstract: This study investigated the role of flaxseed meal (FSM), a rich terrestrial source of ω‐3 fatty acids, in the alteration of the fatty acid profile and metabolism, health indices, physicochemical properties, and sensory quality of broiler chicken meat. The broiler chickens were fed 100 g FSM kg −1 diet for different time periods (1, 2, 3, 4, and 5 weeks). The results revealed that 100 g FSM feeding in broiler chickens for at least 3 weeks increased ( P < 0.01) the EPA, DHA, MUFA, PUFA, ω‐3 PUFA, and ω‐6 PUFA of broiler chicken meat with the corresponding decrease in palmitic acid, stearic acid, and SFA content. 100 g FSM feeding up to 3 weeks has increased the Δ 9 ‐desaturases ( P < 0.05), thioesterase index ( P < 0.01), and Δ 5 ‐desaturase + Δ 6 ‐desaturase activity ( P < 0.01) along with an improvement in health indices ( P < 0.01) of chicken meat. Similarly, a reduction in meat cholesterol and fat content of thigh meat ( P < 0.01) was observed by feeding 100 g FSM for at least 3 weeks with no effect on the pH, color scores, and sensory evaluation of broiler chicken meat. The water‐holding capacity (WHC) and extract release volume (ERV) decreased, whereas, drip loss of meat increased ( P < 0.01) due to the feeding of 100 g FSM beyond 3 weeks. Thus, this study concluded that 100 g FSM feeding for 3 weeks in broiler chickens significantly improves the fatty acid profile, lipid metabolism, and health indices of meat, without compromising the physicochemical properties of broiler chicken meat.